2021
DOI: 10.1038/s41598-021-98506-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional connectivity of the ascending arousal network for prediction of outcome in patients with acute disorders of consciousness

Abstract: To determine the role of early acquisition of blood oxygen level-dependent (BOLD) signals and diffusion tensor imaging (DTI) for analysis of the connectivity of the ascending arousal network (AAN) in predicting neurological outcomes after acute traumatic brain injury (TBI), cardiopulmonary arrest (CPA), or stroke. A prospective analysis of 50 comatose patients was performed during their ICU stay. Image processing was conducted to assess structural and functional connectivity of the AAN. Outcomes were evaluated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Previous studies have already demonstrated a strong signature of the underlying structural network in functional networks in DoC. However, these previously described functional networks were mostly obtained using time-averaged estimation methods ( Annen et al, 2016 ; Enciso-Olivera et al, 2021 ; Kuceyeski et al, 2016 ; Lant et al, 2016 ), and have not provided insight into a stronger structural functional coupling in DoC. Using time-resolved functional connectivity and its relationship to eigenmodes, we shed light on this observation.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have already demonstrated a strong signature of the underlying structural network in functional networks in DoC. However, these previously described functional networks were mostly obtained using time-averaged estimation methods ( Annen et al, 2016 ; Enciso-Olivera et al, 2021 ; Kuceyeski et al, 2016 ; Lant et al, 2016 ), and have not provided insight into a stronger structural functional coupling in DoC. Using time-resolved functional connectivity and its relationship to eigenmodes, we shed light on this observation.…”
Section: Discussionmentioning
confidence: 83%
“…Our cohort also included a relatively low proportion of patients with an acute, behavioral diagnosis of VS (5%). Recent studies investigating patients with acute DoCs enrolled widely varying proportions of patients with behavioral VS diagnoses (range: 11–41%) ( Claassen et al, 2019 ; Enciso-Olivera et al, 2021 ; Kondziella et al, 2017 ; Othman et al, 2021 ; Seel et al, 2013 ). The timing of post-injury behavioral assessments in such studies is also often variable.…”
Section: Discussionmentioning
confidence: 99%
“…When assessing structural integrity, methodological considerations become critical due to the extent and heterogeneity of lesions in DoC patients. A variety of approaches have been used, broadly classified in quantitative approaches, using automated or semi‐automated algorithms, 11–13 and qualitative approaches, based on neuroradiologists' ratings 5,6,14–16 …”
Section: Introductionmentioning
confidence: 99%
“…6 When assessing structural integrity, methodological considerations become critical due to the extent and heterogeneity of lesions in DoC patients. A variety of approaches have been used, broadly classified in quantitative approaches, using automated or semi-automated algorithms, [11][12][13] and qualitative approaches, based on neuroradiologists' ratings. 5,6,[14][15][16] The quantitative methods are user-independent, providing an unbiased measure, but are sensitive to MRI artifacts or anatomical deformations that can determine the exclusion of a potentially high number of patients (up to 35%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation